A Perspective on the Use of Limited-Dependent and Qualitative Variables Models in Accounting Research. - Maddala, G.S. (The Accounting Review, 1991)
Reviews the methodology of models involving qualitative and limited-dependent variables and their application in accounting research. Logit and probit models and discriminant analysis; Tobit model and the truncated regression model; Models involving sample selection bias; Models involving self-selectivity; Prediction of the effects of mandated accounting changes.